Prediksi Pertumbuhan Penduduk Kecamatan Cimaragas Kabupaten Ciamis Dengan Metode Artificial Neural - ARMANDA, RAFLI KURNIA (Algoritme Jurnal Mahasiswa Teknik Informatika, 2023)
This research was conducted to study an Artificial Neural Network, which is one of the command languages used in the Matlab program which is used to predict input data and can be used to predict population growth. Artificial Neural Network is a powerful data model that is able to capture and represent complex Input-Output relationships, because of its ability to solve some problems relatively easy to use, resilience to input speed data for execution, and initialize complex systems. By using Artificial Neural Networks (Artificial Neural Network) is expected to provide another alternative in estimating and predicting population growth rates in Cimaragas District, Ciamis Regency.